Paediatric Residents Training in Pakistan: Time for a Paradigm Shift - Aisha Mehnaz (Journal of the Pakistan Medical Association, 2023)
Madam, I fully concur with the comments made by my Physical Medicine colleague/s. Paediatric residents training need a 360 degree evaluation and change with focus on need assessment , curriculum change and revolutionary changes in training methodology, the latter should be more on-site rather than contextual. At present both the teaching and practical skills of paediatric residents in Pakistan are suboptimal. The clinical skills of our residents are particularly are far from satisfactory. They particularly lack in soft skills, behavioural and developmental problems assessment, critical thinking and reasoning. In order to identify strengths and gaps in training of our residents, proper planning and discussion are needed with a view to develop strategies for addressing the gaps. Continue...